A googness of-fit-test for a multivariate errors-in-variables model - Kukush, A.; Polekha, M. (Інститут математики НАН України, 2006)
A multivariate errors-in-variables model AX ≈ B is considered, where the data matrices A and B are observed with errors, and a matrix parameter X is to be estimated. A goodness-of-ﬁt test which is based on the moment estimator is constructed. The proposed test is asymptotically chi-squared under null hypothesis. The power of the test is discussed.